Investor Readiness Technical report - Mugo, Purity (CGIAR System Organization, 2024)
Investment readiness in CFSA program is designed to prepare selected agribusinesses through business mentorship, financial literacy, and networking opportunities to help them develop a strong business case, develop scaling plan, and build a compelling investment narrative to attract investment. The Investment Readiness is a 6-month initiative designed to provide support to agribusinesses in East and Southern Africa culminating with a pitch day event where the agribusinesses are hosted together with the investors and have a chance to showcase their businesses and attract funding.